2008
DOI: 10.1017/s0033291708004376
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem volumetric alterations in children with autism

Abstract: BACKGROUND-Although several studies have examined brainstem volume in autism, results have been mixed and no investigation has specifically measured gray and white matter structures. The goal of this investigation was to assess gray and white matter volumes in children with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 32 publications
(54 reference statements)
3
55
0
Order By: Relevance
“…However, this finding is consistent with other recent research suggesting brainstem atypicalities are related to central features of ASD. For example, Jou and colleagues (2009) found that gray matter volume of the brainstem was related to oral sensory sensitivity in ASD and that gray matter volume of the brainstem developed atypically in children and adolescents with ASD (Jou et al 2013). In addition, Cohen and colleagues (I.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is consistent with other recent research suggesting brainstem atypicalities are related to central features of ASD. For example, Jou and colleagues (2009) found that gray matter volume of the brainstem was related to oral sensory sensitivity in ASD and that gray matter volume of the brainstem developed atypically in children and adolescents with ASD (Jou et al 2013). In addition, Cohen and colleagues (I.…”
Section: Discussionmentioning
confidence: 99%
“…In actual fact, structural neuroimaging studies have found few converging results: increased brain volume in ASD, modified GM density or volume in the brainstem,13 amygdala, hippocampus and cerebellum 14. To the best of our knowledge, no papers have attempted to statistically summarise the neuroanatomical results available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, two cross-sectional volumetric MRI investigations observed no differences in the brainstem volume in ASD compared to controls [16, 17]. In contrast, a recent study of brainstem volumes reported reductions in whole brainstem volume and total brainstem gray matter in the group of mainly adult participants with autism [18]. While many studies have examined the brainstem for abnormalities in ASD, the findings remain both inconsistent and inconclusive.…”
Section: Introductionmentioning
confidence: 99%